Veronika Bromová : Zemzoo. - Bienal de Venezia Venezia 12/06-7/11/1999 (Praha AHA Publishing, 1999)
The idea of Zemzoo - meaning Earthzoo - was developed over time, its final form was set thanks to my experience in the heat of New York City in the summer of 1998, during my three month stay at the International Studio Program. The first instance of Zemzoo was exhibited at the end of 1998 in the Prague Gallery Nová sin - the space for which Zemzoo was created, as the gallery reminds one of a gigantic aquarium. Zemzoo was chosen to represent the Czech Republic at the 48th Biennial of Contemporary Art in Venice in 1999.
XLVIII. Biennial in Venice 1999, Zemzoo Veronika Bromova, Pavilion of the Czech Republic, Giardini di Castello, Venice, June 12 - November 7, 1999
biog., ind. tent., gr. tent., prijzen, bibliog., coll. [2 p.]
Engels
boek
Keywords: Bromová, Veronika